Analysis of the Problems of the Substance of State Sharia Securities Contracts from the Perspective of Profit Sharing Principles - Baidhowi; Louisa Grace Gloria Hutagaol; Shely Nayla Putri; Maulana Habibie Yahya; Tania Pakpahan (Takaza Innovatix Labs Ltd., 2025)
The issuance of State Sharia Securities (SBSN) represents the state's effort to provide financing instruments aligned with Sharia principles. However, the use of ijarah contracts with predetermined returns raises questions regarding their conformity with the profit-and-loss sharing principle, which is a fundamental characteristic of Islamic finance. This study aims to analyze whether the substantive structure of SBSN contracts reflects the profit-and-loss sharing principle and to assess the relevance of such contracts within the Islamic financial system. This research employs a normative legal method using statutory and conceptual approaches through library research. The research instrument consists of a document study guideline, while data are analyzed using qualitative interpretative and argumentative techniques. The results show that, although SBSN contracts formally comply with Sharia requirements, their fixed-return structure indicates that the profit-and-loss sharing principle is not substantively implemented. This suggests that SBSN reflects formal compliance rather than a comprehensive application of core Islamic economic principles.